2015
DOI: 10.1007/s10072-015-2386-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral insulin, insulin signaling pathway, and brain angiogenesis

Abstract: Insulin performs unique non-metabolic functions within the brain. Broadly speaking, two major areas of these functions are those related to brain endothelial cells and the blood-brain barrier (BBB) function, and those related to behavioral effects, like cognition in disease states (Alzheimer's disease, AD) and in health. Recent studies showed that both these functions are associated with brain angiogenesis. These findings raise interesting questions such as how they are linked to each other and whether modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 71 publications
(98 reference statements)
0
32
0
Order By: Relevance
“…Thus, our results were consistent with those of previous experiments. Previous studies have demonstrated that the PI3K/Akt signalling pathway and TNF-α played vital roles in neural development 41 , 42 . Some studies also have shown that miR-199a-5p can regulate PI3K and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results were consistent with those of previous experiments. Previous studies have demonstrated that the PI3K/Akt signalling pathway and TNF-α played vital roles in neural development 41 , 42 . Some studies also have shown that miR-199a-5p can regulate PI3K and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to IGF1, insulin is involved in modifying BBB permeability in the brain[ 55 ] with T2D patients showing greater permeability of the BBB[ 67 ]. Insulin also acts on the PI3K and MAPK signaling cascades to enhance neuronal survival, plasticity, and subsequent cognitive processes[ 55 , 68 , 69 ]. With that said, insulin does not necessarily regulate glucose activity in neuronal cells after entering the brain.…”
Section: The Igf1 Systemmentioning
confidence: 99%
“…The inability to recover from stress predisposes us to many neurological dysfunctions, such as post-traumatic brain injuries and neurodegeneration [reviewed in (Blázquez et al, 2014;Esch et al, 2002;Frey, 2013;Koenen et al, 2008;Zeng et al, 2016)]. Here we use the worm C. elegans to elucidate the mechanisms of stress adaptation and recovery, since the worm can switch its the nerve ring (NR) bundle ( Figure S1A), where the axons synapse to each other (White et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…physiological state in response to stress [reviewed in (Riddle and Albert, 1997)]. Like in humans [(Blessing et al, 2017;Marcovecchio and Chiarelli, 2012); reviewed in (Bedse et al, 2015;Blázquez et al, 2014;Boucher et al, 2014;Frey, 2013;Zeng et al, 2016)], insulin-like peptides (ILPs) and their receptor enable the worms to endure and recover from stress (Kimura et al,…”
mentioning
confidence: 99%